ECONOMIC HISTORY OF REGIONAL INDUSTRIALIZATION ([S.l.])
1 online resource
Keywords: This book offers a comprehensive study of regional industrialization in Europe and Asia from the early nineteenth century to the present. Using case studies on regional industrialization, the book provides insights into similarities and differences in industrialization processes between European, Eurasian and Asian countries. Important factors include the transition from traditional to modern industrial production, industrial policy, agglomeration forces, market integration, and the determinants of industrial location over time. The book is an invaluable reference that attempts to bridge the fields of economic history, political history, economic geography, and economics while contributing to the debates on economic divergence between Europe and Asia as well as on the role of economic integration and globalization.